THE EFFECT OF PSYCHOLOGICAL AND HEALTH EDUCATION APPROACHES BASED ON SELF-EFFICACY ON COMPLIANCE WITH TUBERCULOSIS PATIENT: A SYSTEMATIC REVIEW - Idham Choliq; Tintin Sukartini; Makhfudli Makhfudli (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: One of the obstacles to TB management today has been non-compliance. Non-compliance of TB patients in treatment can be influenced by the perception of self-efficacy.Objective: The study aimed to analyze the effect of psychological and health education approaches based on self-efficacy on adherence with tuberculosis patients.Design: Design research uses systematic review based on PRISMA checklist.Data Sources: Using three databases: Scopus, Science direct, and CINAHL. The three databases are of high and medium reputation. The search was conducted from June to July 2020. The keywords in this systematic review are “mycobacterium tuberculosis” OR